A informalidade, uma resposta do projeto societário capitalista à questão social desemprego: o caso dos ex-bancários do Banestado em Cascavel - Alves, Pedro (2005)
This essay is the result of a study of choices among the alternatives that ex-bank workers of Banco do Estado do Paraná Banestado in Cascavel, who were laid off from this financial institution between 1995 and 2001. By delimiting the object within the realm of a case study, our research was delineated around understanding and analyzing, with the help of quantitative and qualitative methodological-theoretical elements based on a macro-societal, Marxian and of Marxist tradition reference content, highlighting the work The Delayed Capitalism by Ernest Mandel. The objective of this study is to understand and analyze the conditions in which these workers are today, by focusing specifically on those that are inserted in the informality realm, in the so-called autonomous or self sufficient and informal small business owner sub-sectors. At the same time, we supported these fundaments with specific literature, thus allowing us, by means of a Marxist orthodoxy, to rebuild the object in question, which made us understand that the worker, be it at the formal or informal realm, is subordinated to the capitalistic way of production, selling its merchandise work force and keeping the regime afloat. On the other hand, the informal workers who originated from the bank worker s class, find themselves in precarious conditions as far as the social, political and economic points of view are concerned, when compared with the prior working bond in the financial sector. Thus, we have identified in our research that the teleological project of the bank s ex-workers have been altered, although it did no alter the negation degree in their objective and subjective relations.